High genetic diversity in the harvestman Geraeocormobius sylvarum (Arachnida, Opiliones, Gonyleptidae) from subtropical forests in northeastern Argentina revealed by mitochondrial DNA sequences - Vaschetto, Luis Maria Benjamin (2015)
This research was aimed to analyse the genetic diversity of Geraeocormobius sylvarum, a forest-dwelling Neotropical harvestman with a disjunct distribution,separated by approximately 630 km of semi-arid environments. The usefulness of a fragment of the cytochrome c oxidase subunit I (COI) mitochondrial gene as molecular marker was tested in 109 individuals. Results showed high levels of both haplotype and nucleotide diversity in populations corresponding to north-eastern Argentina, the core area of the species range. A strong genetic structuring was detected, supported by both the phylogenetic trees and the haplotype network, with six identifiable haplogroups. Populations of the Yungas ecoregion did not show significant diversity levels, suggesting a putative recent introduction of the species into that region. The overall results suggest that the present genetic diversity of the species is consistent with past fragmentation events of the species range (in refuges?), probably during the Last Glacial Maximum. The COI gene was concluded to be a well-suited marker to associate past environmental events with the high genetic diversity observed in this species.